Blogging the Writers Strike: Identity, Interaction and Engagement for Collective Action. (1st October 2010) - Nina O'Brien
Abstract : This study examines the role of weblogs as sites for negotiating collective identity, arguing that strategic deployment of blogs may encourage greater identification with collective actions by a wider variety of individuals. This case study of the Writers Guild of America blog United Hollywood, shows that its structure and publication policies were successful in mobilising a variety of stakeholders to identify as a collective. Qualitative analysis of form and content suggests that the communality provided by the blog allowed the WGA to leverage benefits of traditional institutional collective action space and to augment these with benefits provided by hybrid forms of online organisation.